2021
DOI: 10.5812/jjnpp.106447
|View full text |Cite
|
Sign up to set email alerts
|

Magnolia officinalis Ameliorates Dehydroepiandrosterone-Induced Polycystic Ovary Syndrome in Rats

Abstract: Background: Polycystic ovary syndrome (PCOS) is a prevalent reproductive and metabolic disorder. Insulin resistance (IR) is highly associated with PCOS and aggravates its symptoms. Thiazolidinediones (TZDs), as insulin sensitizing agents, are PPARγ agonists that improve many of the symptoms of PCOS. The Magnolia officinalis extract (MOE) is a natural peroxisome proliferator activated receptor gamma (PPARγ) agonist that improves insulin sensitivity in experimental models. Objectives: Using a dehydroepiandroster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…In another study, the same animal model of PCOS and insulin resistance was treated with magnolia extract. The obtained results revealed that this extract led to the decrease in the serum insulin and testosterone levels and the increase in the ovarian expression of IRS1, PKB and PPARγ [63]. Both these studies demonstrate that magnolol and magnolia extract are natural PPAR-γ agonists [46,63].…”
Section: Magnolol and Reproductive System Disturbancesmentioning
confidence: 68%
“…In another study, the same animal model of PCOS and insulin resistance was treated with magnolia extract. The obtained results revealed that this extract led to the decrease in the serum insulin and testosterone levels and the increase in the ovarian expression of IRS1, PKB and PPARγ [63]. Both these studies demonstrate that magnolol and magnolia extract are natural PPAR-γ agonists [46,63].…”
Section: Magnolol and Reproductive System Disturbancesmentioning
confidence: 68%
“…PCOS and weight gain were associated with DHEA injections. There is a lot of evidence linking PCOS and being overweight [ 27 ]. In this study, the BW of mice treated with DHEA was significantly increased due to abdominal fat compared to the normal mice [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…After blood collection, animals were euthanized with an overdose of ketamine and their ovarian weight, size, and morphology were assessed [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…These compounds through antioxidant, anti‐inflammatory and apoptotic pathways help to stimulate the onset of normal ovarian cycles, HPO (Hypothalamic–Pituitary‐Ovarian axis) (regulation of androgens and modulation of LH/FSH level), mitochondrial apoptosis of granulosa cells and eventually ovulation in PCOS patients (Jazani, Azgomi, Azgomi, & Azgomi, 2019). Nassar, Khachab, Zaatiti, and Kanaan (2021) showed that Magnolia officinalis L. extract in DHEA‐induced PCOS in rats regulated the ovarian cycle and normal ovulation by reducing the LH/FSH ratio and stimulating the IRS‐1 and AKT pathways (Nassar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds through antioxidant, anti-inflammatory and apoptotic pathways help to stimulate the onset of normal ovarian cycles, HPO (Hypothalamic-Pituitary-Ovarian axis) (regulation of androgens and modulation of LH/FSH level), mitochondrial apoptosis of granulosa cells and eventually ovulation in PCOS patients (Jazani, Azgomi, Azgomi, & Azgomi, 2019). Nassar, Khachab, Zaatiti, and Kanaan (2021) showed that Magnolia officinalis L. extract in DHEA-induced PCOS in rats regulated the ovarian cycle and normal ovulation by reducing the LH/FSH ratio and stimulating the IRS-1and AKT pathways(Nassar et al, 2021).Nasturtium officinale L. (N. officinale) or Watercress belongs tothe Brassicaceae and aquatic family, with a height of 20-80 cm and simple leaves that are native to Eastern Europe, Southeast Asia and the Middle East. The leaves of this plant are used as a vegetable in soups, stews, teas and additives in various foods.…”
mentioning
confidence: 99%